Clinical management of thromboembolic events arising from complications of COVID-19: integrative review (Research, Society and Development, 2021)
Objective: to identify how the clinical management of patients infected with COVID-19 who present pulmonary thromboembolism and/or venous thromboembolism occurs. Method: This is an integrative review, carried out by searching for articles in the VHL, LILACS, MEDLINE, CINAHL AND SCOPUS databases, with a temporal delimitation from November 2019 to March 2021. Results: 24 articles were included. Diagnosis occurs through D-dimer and fibrinogen. For drug therapy, low molecular weight heparin (LMWH) is administered, 30 mg/12h in 12h for prophylactic anticoagulation, staggered doses of LMWH with enoxaparin, 0.5 mg/kg twice a day for anticoagulation therapy and rivoxaban 10mg/day for post-discharge anticoagulation. Conclusion: Clinical management of TEP and VTE occurs through increased D-dimer or fibrinogen, with TEP confirmed by pulmonary angiography. For anticoagulation, LMWH is mostly used.